Design and development of a tubular solar distiller using a convex absorber, wick materials, and PCM reservoir combined with a solar parabolic concentrator. (June 2023) - Bacha, Habib Ben; Abdullah, A.S.; Kabeel, Abd Elnaby; Abdelgaied, Mohamed
Abstract: Water scarcity is a real threat facing many countries, especially the MENA region, and it is rapidly increasing as a result of rapid population growth and climate change. Solar distillers are one of the applications of cleaner production and a suitable solution for future technologies, but they still need a lot of research efforts to reach the competitive level with traditional desalination technologies. Therefore, this study aims to present an innovative design of tubular solar distillers with higher productivity and the lowest possible cost. This was done by adding a convex absorber instead of the flat absorber, as well as covering it with black jute wick material, in addition to using an energy storage reservoir below the convex absorber that contains paraffin wax and the oil heat exchanger incorporated with solar parabolic concentrator which represents the additional heat source. To evaluate the performance of the proposed innovative configuration of a tubular solar distiller, two tubular solar distillers were designed and tested in Al-Kharj, Saudi Arabia. The first is a conventional tubular solar distiller (CTSD) which represents a reference distiller. The second is a modified convex tubular solar distiller (MCVTSD). The results showed the high productivity of the MCVTSD, which reached 13.58 L/m 2 /day. Where, the innovative configuration of MCVTSD improved productivity, and thermal and exergy efficiencies by 233.25 %, 39.32 %, and 4.99 %, respectively as compared to CTSD. The economic feasibility presented that the utilization of MCVTSD led to a decrease in the distilled water production cost by 44.55 % compared to CTSD. Highlights: Designed and developed a tubular solar distiller that has higher productivity and the lowest cost Performance of a developed tubular distiller using a wick convex absorber, PCM reservoir, and solar concentrator was studied The improvement in the productivity of the developed tubular distiller reached 233.25 % The improvement in the thermal and exergy efficiencies reached 39.32 % and 4.99 %, respectively The developed design of a tubular distiller reduced the distillate water cost by 44.55 %